Extended Pelvic Resections as Part of Secondary Cytoreduction for Relapsed Ovarian Adenocarcinoma - BACALBASA, NICOLAE (In Vivo, 2020)
Background/Aim: Ovarian cancer presents an aggressive tumor biology, a significant number of patients experiencing recurrent disease. The aim of this study was to examine the feasibility and effectiveness of secondary debulking surgery for relapsed ovarian cancer. Patients and Methods: Between 2014 and 2018, debulking surgery for relapsed ovarian cancer was performed in 40 cases. Results: Debulking surgery to no residual disease was achieved in 31 cases; among the remaining cases, an R1 resection was feasible in six cases, while in the remaining three cases an R2 resection was performed. The most commonly performed visceral resections were represented by rectosigmoidian resection, right colon resection, total or partial cystectomy and unilateral or bilateral ureteral resection. The early postoperative morbidity rate was 32.5% while the postoperative mortality rate was 2.5%. Conclusion: Extended pelvic resections are feasible in patients with relapsed ovarian cancer and might be performed with acceptable rates of postoperative complications.